Coast to coast: discovering local distinctiveness of marketplaces identity in Peninsular Malaysia / Raziah Ahmad ... [et al.] - Ahmad, Raziah; Mohamed Anuar, Mohamed Ikhwan Nasir; Ab Rahman, Zainuddin; Zakaria, Muhammad Adam; Abdullah, Jamalunlaili (UiTM Press, 2022)
Modernisation in Malaysia has greatly influenced the local identity of urban and rural places. Hence, there is increasing concern that the homogenising effect of the place character has affected the individuality of places. Local distinctiveness is closely linked to a place's physical and social ambiance, differentiating it from anywhere else. The notion of marketplaces in Malaysia relating to place identity has gained proper attention from local researchers. However, the correlation of physical and non-physical elements of marketplaces in creating local distinctiveness is still under-explored. This research aims to discover the overt and covert marketplaces of the West Coast and East Coast of Peninsular Malaysia. The objectives are to explore how the overt and covert parameters contribute to and enhance the local distinctiveness of the marketplace's identity. This study employs a qualitative approach through direct non-participant observation and cultural mapping at the four selected marketplaces: Pantai Suri floating market in Tumpat, Kelantan, Pasar Bisik in Penaga, Penang, Pasar Jerami in Sungai Besar, Selangor, and Pasar Borneo in Masai, Johor. The overt and covert of each market were carefully observed and mapped, where three substantial outcomes were revealed. First, the market's social interaction-transaction, social activities, and social connectivity portray the covert parameters as vital for creating local distinctiveness. Second, marketplaces have the potential as dynamic community public spaces to get fresh dairy products and promote local heritage and tourism. Third, marketplaces face threats from climate change, pandemic Covid-19, and the diminishing local culture and traditions. In conclusion, the covert and overt marketplaces should be equally preserved as they become primary components for establishing the local distinctiveness of place identity.